Setting the tone : the impact of music on fatigue, arousal and motivation during conditioning for high to elite level female artistic gymnasts - Lotter, Carol Barbara (University of Pretoria, 2021)
Dissertation (MMus (Musicology))--University of Pretoria, 2019.